Renovación de pasturas degradadas de kikuyo pennisetum clandestinum, hoechst, con labranza mínima en una región alto andina de colombia i. productividad forrajera. (2004)
Se utilizaron tres métodos de renovación de pasturas degradadas: (Kikuyo sin labranza mínima, KSLM; Kikuyo con labranza mínima, KLM, y kikuyo con labranza mínima más la aplicación de fertilización química y siembra de tréboles, KLMFS) en período lluvioso y seco; se incluyó como testigo (T) el manejo tradicional de la pastura en la finca. La disponibilidad de forraje verde seco fue mayor en KLM y KLMFS en el período lluvioso (962 y 735 kg/ha) que en el seco (505 y 378 kg/ha), respectivamente. La capacidad de carga en los métodos con labranza mínima se estimó en 2.5 UA/ha (5 vacas) en el período de lluvias y de 1.2 y 1.4 U.A/ha (4 vacas) en el período seco. En los métodos sin labranza mínima fue de 0.1 y 2 U.A/ha (1 y 4 vacas) en el período de lluvias y de 0.1 y 0.4 U.A/ha (1 vaca) en el período seco. ABSTRACT Renovation of pastures degraded the kikuyo pennisetum clandestinum, Hoechst, with minimum tillage in an andean high region de Colombia I. Productivity forrajera. Three methods of renewal of degraded pastures were used (Kikuyo without minimum tillage of pasture, KSLM; Kikuyo with minimum tillage, KLM and Kikuyo with minimum tillage more the application of chemical fertilization and clovers seeds, KLMFS), in rainy period and dry off; as a control it was included the traditional method of forage management in the farm (T). The availability of the green forage, was bigger in KLM and KLMFS in the rainy period (962 and 735 kg/ha) that in the dry period (505 and 378 kg/ha). The load capacity in the methods with minimum farm you estimates in 2.5 UA/ha (5 cows) in the period of rains and of 1.2 and 1.4 U.A/ha (4 cows) in the dry period. In the methods without minimum farm was of 0.1 and 2 U.A/ha (1 and 4 cows) in the period of rains and of 0.1 and 0.4 U.A/ha (1 cow) in the dry period. Key words: Kikuyo grass, Pennisetum clandestinum Hoechst, pasture renewal, minimum tillage, Hills, Forage productivity, Cattle Use, High Andean Región.